Analisis Potensi Kontribusi Pajak Rumah Kos Terhadap Pendapatan Asli Daerah Di Kabupaten Mimika (Studi Kasus Di Distrik Mimika Baru) - Febrianto, Rachmad Eryan; Pabendon, Tharsisius (STIE Jambatan Bulan, 2023)
This study aims to determine the potential contribution of boarding house taxes to local revenue in Mimika Regency, especially in Mimika Baru District. The analytical method used is descriptive. Data collection techniques in this study were observation and interviews with 34 boarding house owners with 10 rooms in Mimika Baru District. The instrument used in data analysis is the analysis of potential contributions with the aim of measuring each potential and contribution that can increase Regional Original Income. The results of the study show that the potential for boarding house taxes in the Mimika Baru District is quite large, namely IDR 407,386,800 per year with a very low contribution or 0.37%, but this potential does not yet cover all the boarding house taxpayers in each district. Mimika Regency. If all districts in Mimika Regency pay taxes, it can certainly make a big contribution to increasing the Regional Original Income